Ruled Surfaces as Pseudospherical Congruences - Gorkavyy, V.O.; Nevmerzhitska, O.M. (Журнал математической физики, анализа, геометрии, 2009)
Two-dimensional ruled surfaces in the spaces of constant curvature Rⁿ, Sⁿ, Hn and in the Riemannian products Sⁿ x R¹, Hⁿ x R¹ are considered. A ruled surface is proved to represent a pseudospherical congruence if and only if it is either an intrinsically flat surface in Sⁿ, or an intrinsically flat surface with constant extrinsic curvature in Sⁿ x R¹.